2019
DOI: 10.1186/s13073-019-0674-2
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory cytokines and organ dysfunction associate with the aberrant DNA methylome of monocytes in sepsis

Abstract: BackgroundSepsis, a life-threatening organ dysfunction caused by a dysregulated systemic immune response to infection, associates with reduced responsiveness to subsequent infections. How such tolerance is acquired is not well understood but is known to involve epigenetic and transcriptional dysregulation.MethodsBead arrays were used to compare global DNA methylation changes in patients with sepsis, non-infectious systemic inflammatory response syndrome, and healthy controls. Bioinformatic analyses were perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
63
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(65 citation statements)
references
References 43 publications
2
63
0
Order By: Relevance
“…RNA sequencing revealed a clear separation of samples from healthy individuals and samples from ICU patients (see Figure 3B). A recent study nicely demonstrated widespread changes in the methylome of circulating monocytes from septic patients with the acquisition of a tolerized phenotype and organ dysfunction [43].…”
Section: Discussionmentioning
confidence: 95%
“…RNA sequencing revealed a clear separation of samples from healthy individuals and samples from ICU patients (see Figure 3B). A recent study nicely demonstrated widespread changes in the methylome of circulating monocytes from septic patients with the acquisition of a tolerized phenotype and organ dysfunction [43].…”
Section: Discussionmentioning
confidence: 95%
“…Sepsis is defined as life-threatening organ dysfunction caused by a deregulated systemic immune response to infection. Interestingly, DNA methylation changes have been associated with sepsis in monocytes, which correlated with inflammatory signals [133]. Besides, chromatin modifications have been implicated in the regulation of the cellular immune/inflammatory responses in patients with sepsis [134].…”
Section: Infectionsmentioning
confidence: 99%
“…This was reflected by an early increase of myeloid PD-L1 expression, lymphocytic apoptosis and macrophage anergy with loss of antigen-presenting capacity ( Hotchkiss and Nicholson, 2006 , Huang et al, 2014 , Landelle et al, 2010 ). Usually, sepsis acquired immunodeficiency is accompanied by cytokine-related T cell exhaustion, release of myeloid suppressor cells and epigenetically determined monocyte switch to endotoxin tolerance after bacterial stress ( Biswas and Lopez-Collazo, 2009 , Boomer et al, 2011 , Cheng et al, 2016 , Lorente-Sorolla et al, 2019 ). Thus, methylation-related predisposition for immune memory adaption may influence the highly variable outcome and affect later immunity in patients with severe bacterial co-infection of COVID-19 pneumonia to a varying extent.…”
Section: Discussionmentioning
confidence: 99%